ETIKA PENGGUNAAN MEDIA SOSIAL SESUAI SILA KEDUA - Gita Dwi Mutia; Mainar Fitri; Rike Juliansari; Eva Siti Fadilla (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The increasingly massive use of social media requires special attention to the ethics carried out by its users. The second principle of Pancasila, "Just and Civilized Humanity," emphasizes the importance of respecting human values, justice and morality in social interactions, including in the digital world. In the context of social media, ethical use in accordance with the second principle includes mutual respect, maintaining good manners, and not spreading hate speech, hoaxes, or content that harms other people. Users are expected to be able to show empathy, care about the welfare of others, and uphold fairness in interactions. This research aims to analyze the importance of applying ethics based on the second principle of Pancasila in maintaining harmony and morality in the digital space, as well as the positive impact of its application on the quality of social communication.